Role of pulse radiofrequency and radiofrequency in trigerminal neuralgia pain management: card up your sleeve - Mohamed, Rozilah @ Abdul Hadi; Abdullah, Nor Zamzila; Lukman, Mohd Fahmi; Ahmad, Mohd Ashri; Mat Nor, Mohd Basri; Osman, Ariff (Thailand Association for the Study of Pain, 2011)
Chronic Pain is major public health problem that is associated with reduced in quality of life and great loss to the nation. Oral analgesics are considered as first-line treatment along with physiotherapy and psychological therapy. When pharmacology treatment or conventional surgery fails to control the chronic pain, minimally invasive interventional procedures become an option as to control the pain and to prevent the potential side effects due to high dose of analgesics. The first step involves the identification of target nerve through prevention of neuronal transmission by blocking the membrane ion channels using local anaesthetics or steroids which act as anti-inflammatory agent. Once the target nerve or source of pain has been identified, therapeutic minimally invasive pain intervention was carried out. The procedure can be performed by direct denervation using chemicals such as alcohol or phenol or physical methods such as cryolesioning or radiofrequency lesioning which lead to protein denaturation of axons. This procedure gave a temporary or permanent relief for chronic pain patients by reversibly interfering with neuronal transmission or eliminating the source of pain. As a result, muscle spasm vanishes and ranges of mobility increases. This facilitates physical therapy and rehabilitation. This is the mechanism in which minimally invasive pain intervention breaks up the pain cycle and aids the relief of pain symptoms. We presented two cases of trigeminal neuralgia who failed conservative treatment. Both of them were successfully treated with radiofrequency and pulse radiofrequency.